Konsekwencje finansowe wprowadzenia podatku dochodowego w indywidualnych gospodarstwach rolniczych - Gruziel, Kinga (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
In the study an attempt at describing financial consequences of income tax introducing in individual farms situated in FADN regions Wielkopolska i Śląsk and Mazowsze i Podlasie was made. The highest profits from income tax introducing were stated in agricultural farms type “crops” and “crops and various animals”. The highest burden from income tax introducing for hectare of arable land would occurred in agricultural farms type “granivores” especially of the area 5–15 hectares of arable land